Measuring and auditing broiler welfare [ - Butterworth, A. [ (Andrew)]; Weeks, C. [ (Claire)] (CABI, 2004)
In response to concerns about animal welfare, food assurance schemes are now incorporating standards for animal welfare. This is particularly important in the poultry industry, where much attention has focused on the welfare of brollers (meat birds).